(untitled) - Giddens, Anthony (New York, 2006)
The best-selling Introduction to Sociology is now available in an abridged edition. Featuring a striking design, helpful pedagogy, and a global perspective, Essentials of Sociology packages the best facets of the Fifth Edition of Introduction to Sociology in a shorter, more flexible edition. With fewer topics covered in only sixteen chapters, students can focus on the essentials while learning about the connections between American and world societies. An in-text study guide and extensive student Web site help students study and review, while online instructor's resources assist with teaching and grading.
Keywords: Sociology,Xã hội học